If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 = 12((5 + -1x) + x + (4 + -1x)) + 10 + -1((5 + -1x) + x + (6 + -1x)) + 11 + -1((4 + -1x) + x + (6 + -1x)) Remove parenthesis around (5 + -1x) 20 = 12(5 + -1x + x + (4 + -1x)) + 10 + -1((5 + -1x) + x + (6 + -1x)) + 11 + -1((4 + -1x) + x + (6 + -1x)) Remove parenthesis around (4 + -1x) 20 = 12(5 + -1x + x + 4 + -1x) + 10 + -1((5 + -1x) + x + (6 + -1x)) + 11 + -1((4 + -1x) + x + (6 + -1x)) Reorder the terms: 20 = 12(5 + 4 + -1x + x + -1x) + 10 + -1((5 + -1x) + x + (6 + -1x)) + 11 + -1((4 + -1x) + x + (6 + -1x)) Combine like terms: 5 + 4 = 9 20 = 12(9 + -1x + x + -1x) + 10 + -1((5 + -1x) + x + (6 + -1x)) + 11 + -1((4 + -1x) + x + (6 + -1x)) Combine like terms: -1x + x = 0 20 = 12(9 + 0 + -1x) + 10 + -1((5 + -1x) + x + (6 + -1x)) + 11 + -1((4 + -1x) + x + (6 + -1x)) 20 = 12(9 + -1x) + 10 + -1((5 + -1x) + x + (6 + -1x)) + 11 + -1((4 + -1x) + x + (6 + -1x)) 20 = (9 * 12 + -1x * 12) + 10 + -1((5 + -1x) + x + (6 + -1x)) + 11 + -1((4 + -1x) + x + (6 + -1x)) 20 = (108 + -12x) + 10 + -1((5 + -1x) + x + (6 + -1x)) + 11 + -1((4 + -1x) + x + (6 + -1x)) Remove parenthesis around (5 + -1x) 20 = 108 + -12x + 10 + -1(5 + -1x + x + (6 + -1x)) + 11 + -1((4 + -1x) + x + (6 + -1x)) Remove parenthesis around (6 + -1x) 20 = 108 + -12x + 10 + -1(5 + -1x + x + 6 + -1x) + 11 + -1((4 + -1x) + x + (6 + -1x)) Reorder the terms: 20 = 108 + -12x + 10 + -1(5 + 6 + -1x + x + -1x) + 11 + -1((4 + -1x) + x + (6 + -1x)) Combine like terms: 5 + 6 = 11 20 = 108 + -12x + 10 + -1(11 + -1x + x + -1x) + 11 + -1((4 + -1x) + x + (6 + -1x)) Combine like terms: -1x + x = 0 20 = 108 + -12x + 10 + -1(11 + 0 + -1x) + 11 + -1((4 + -1x) + x + (6 + -1x)) 20 = 108 + -12x + 10 + -1(11 + -1x) + 11 + -1((4 + -1x) + x + (6 + -1x)) 20 = 108 + -12x + 10 + (11 * -1 + -1x * -1) + 11 + -1((4 + -1x) + x + (6 + -1x)) 20 = 108 + -12x + 10 + (-11 + 1x) + 11 + -1((4 + -1x) + x + (6 + -1x)) Remove parenthesis around (4 + -1x) 20 = 108 + -12x + 10 + -11 + 1x + 11 + -1(4 + -1x + x + (6 + -1x)) Remove parenthesis around (6 + -1x) 20 = 108 + -12x + 10 + -11 + 1x + 11 + -1(4 + -1x + x + 6 + -1x) Reorder the terms: 20 = 108 + -12x + 10 + -11 + 1x + 11 + -1(4 + 6 + -1x + x + -1x) Combine like terms: 4 + 6 = 10 20 = 108 + -12x + 10 + -11 + 1x + 11 + -1(10 + -1x + x + -1x) Combine like terms: -1x + x = 0 20 = 108 + -12x + 10 + -11 + 1x + 11 + -1(10 + 0 + -1x) 20 = 108 + -12x + 10 + -11 + 1x + 11 + -1(10 + -1x) 20 = 108 + -12x + 10 + -11 + 1x + 11 + (10 * -1 + -1x * -1) 20 = 108 + -12x + 10 + -11 + 1x + 11 + (-10 + 1x) Reorder the terms: 20 = 108 + 10 + -11 + 11 + -10 + -12x + 1x + 1x Combine like terms: 108 + 10 = 118 20 = 118 + -11 + 11 + -10 + -12x + 1x + 1x Combine like terms: 118 + -11 = 107 20 = 107 + 11 + -10 + -12x + 1x + 1x Combine like terms: 107 + 11 = 118 20 = 118 + -10 + -12x + 1x + 1x Combine like terms: 118 + -10 = 108 20 = 108 + -12x + 1x + 1x Combine like terms: -12x + 1x = -11x 20 = 108 + -11x + 1x Combine like terms: -11x + 1x = -10x 20 = 108 + -10x Solving 20 = 108 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. 20 + 10x = 108 + -10x + 10x Combine like terms: -10x + 10x = 0 20 + 10x = 108 + 0 20 + 10x = 108 Add '-20' to each side of the equation. 20 + -20 + 10x = 108 + -20 Combine like terms: 20 + -20 = 0 0 + 10x = 108 + -20 10x = 108 + -20 Combine like terms: 108 + -20 = 88 10x = 88 Divide each side by '10'. x = 8.8 Simplifying x = 8.8
| 20=(12((5-x)+x+(4-x)))+(10-((5-x)+x+(6-x)))+(11-((4-x)+x+(6-x))) | | 9x-5x-8=360 | | 7x-13-x=5 | | x=5x-25 | | 9x-5x-8= | | 5x+25=7x+50 | | -20z+28=25-16z-12+2z-6z | | y=x^2+m-4x | | 3*2+2=7*2-6 | | 2p+3-3p+8= | | a^2-6a+6=0 | | a^2-8a+b^2-2b+17=0 | | 9a^2-6a+b^2-2b+2=0 | | 35=-10+2x | | 3.7x=0.4 | | (12x^2)+(5x^2)+4x= | | 51+14x=x | | 4*(2x+3)-x*(4-x)=x*(x+1)+3*(x+4) | | 4xsquared-13x+9=-5x+6 | | 9-3k=0 | | 8t-14=0 | | 8m+3n-3m+10n= | | 48x^2-1537x-3076= | | 9x^2-2x^3=0 | | 3f^2+2f-f^2+4f= | | x^3+3x^2-8x+4=0 | | (x+9)2=81 | | 5+y=2y-4 | | 5x^2-30x+9-20x^2-25x+20x^2+5x-5x^2= | | 3x+15=11-x | | 5x*(x-1)= | | 5x*(4x-5)= |